Wandering gallbladder - Kumar, Neeraj; Ranjan, Piyush; Panwar, Rajesh; Kataria, Kamal (International Surgery Journal, 2020)
Cholecystectomy preferably laparoscopy is gold standard treatment for symptomatic cholelithiasis. However for some anatomical and/or pathological reasons the procedure is converted to open. Conversion rates at high volume centres is <5%. We present a case report of 48 aged lady, previously operated multiple times for hydatid liver and lung with symptomatic cholelithiasis. She was planned for laparoscopic cholecystectomy. During the procedure, inadvertent anatomy of “the wandering gallbladder” was noted. Here we describe the management approach selected for this type of unusual presentation. We recommend noting down detailed past history (preferably surgical) and preoperative consideration of deviant anatomical location and findings of gallbladder. We should maintain a low threshold for conversion to open.